Fetal Cardiac Remodeling in Response to Anemia: Using Hemoglobin Bart’s Disease as a Study Model - Theera Tongsong (2018)
Copyright © 2018, Georg Thieme Verlag KG. All rights reserved. Objective To assess fetal cardiac remodeling in response to anemia, by comparing the fetal cardiac dimensions and global sphericity index (GSI) of normal fetuses and fetuses with anemia using fetal Hb Bart’s disease as a study model. Methods Fetuses at risk for Hb Bart’s disease undergoing cordocentesis at 18 to 22 weeks of gestation were recruited. Fetal cardiac dimensions including GSI (cardiac length to cardiac width ratio), interventricular septum thickness (IVST), left ventricular wall thickness (LVWT) and right ventricular wall thickness (RVWT) were measured. Results 215 pregnancies at risk met the inclusion criteria, including 54 affected fetuses and 161 normal fetuses. The mean GSI was significantly lower in the affected group (1.11 ± 0.06 vs. 1.26 ± 0.09, p-value 0.017). The GSI of the normal group was relatively constant regardless of gestational age. The IVST and LVWT tended to increase, but not significantly, in the affected group, whereas the RVWT was minimally but significantly increased. The ROC curve for GSI had an area under curve of 0.844. The best cut-off of GSI was 1.17, giving a sensitivity of 74.1 % and a specificity of 88.2 %. Conclusion Fetal cardiac remodeling in response to anemia causes a marked decrease in global GSI with minimal hypertrophy as an adaption to volume overload. Importantly, GSI is a new maker for anemia and may play a role in clinical application for early detection of fetal anemia, possibly due to any cause. Additionally, GSI measurement is simple and gestational age-independent.